Navigating Life With HIV as an Older Adult on the Kenyan Coast: Perceived Health Challenges Seen Through the Biopsychosocial Model - Patrick N. Mwangala; Patrick N. Mwangala; Patrick N. Mwangala; Ryan G. Wagner; Charles R. Newton; Charles R. Newton; Charles R. Newton; Charles R. Newton; Amina Abubakar; Amina Abubakar; Amina Abubakar; Amina Abubakar (Frontiers Media S.A., 2023)
Objectives: This study explores the perceptions of adults living with HIV aged ≥50 years (recognized as older adults living with HIV-OALWH), primary caregivers and healthcare providers on the health challenges of ageing with HIV at Kilifi, a low literacy setting on the coast of Kenya.Methods: We utilized the biopsychosocial model to explore views from 34 OALWH and 22 stakeholders on the physical, mental, and psychosocial health challenges of ageing with HIV in Kilifi in 2019. Data were drawn from semi-structured in-depth interviews, which were audio-recorded and transcribed. A framework approach was used to synthesize the data.Results: Symptoms of common mental disorders, comorbidities, somatic symptoms, financial difficulties, stigma, and discrimination were viewed as common. There was also an overlap of perceived risk factors across the physical, mental, and psychosocial health domains, including family conflicts and poverty.Conclusion: OALWH at the Kenyan coast are perceived to be at risk of multiple physical, mental, and psychosocial challenges. Future research should quantify the burden of these challenges and examine the resources available to these adults.